Faktor Risiko Penggunaan Ventilator Pada Pasien Covid-19 Di Ruang Icu: Literature Review - Hilalriah, Annisa; Arofiati, Fitri (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
placed great pressure on critical care resources. Identification of patients at high risk for clinical deterioration is critical to ensure access to intensive care for severe conditions in a timely manner. According to (Hajjar et al., 2021), it is stated that in cases of severe respiratory failure, as often seen in ARDS associated with SARS-CoV-2, severe hypoxemia can cause a persistent increase in respiratory effort, with consequent induced lung injury. itself (P-SIL). In addition, other factors such as fluid overload or myocardial injury caused by SARS-CoV-2 can also play an important role in exacerbating the condition through pulmonary congestion. Critical care support optimized by facilitating Covid-19 patients to use ventilators is the best strategy to increase patient survival (Shang et al., 2020). Research Objectives: To determine the risk factors that influence the use of ventilators in COVID-19 patients in the ICU. Research Method: This research uses the literature review method using the Google Scholar, Pubmed, and ProQuest with a time limit for searching articles for 2019-2021, full free text in English and Indonesian and using predefined keywords. Results: The results of this literature review show that there are 3 risk factors that affect the use of ventilators in Covid-19 patients in the ICU, including sociodemographic factors (age, sex, BMI), comorbid factors (two or more co-morbidities), such as diabetes mellitus, hypertension, COPD, cardiovascular, cerebrovascular, and obesity, and lifestyle factors (smoking). Conclusion: The use of ventilators in Covid-19 patients is often used in developed countries as the best strategy to increase patient survival by taking into account the severity of the patient's condition, especially those with respiratory system disorders. In the use of the ventilator there are 3 main factors that must be considered, sociodemographic factors, comorbidity factors, examination results factors, and lifestyle factors.